Infectivity of asexual propagules of Phytophtora infestans in sterile peat exposed to various temperature regimes - Peters, R.D.; Platt, H.W.; Hall, R.. (Phytoprotection, 2000)
Survival of asexual (sporangia and mycelium) propagules of Phytophthora infestans in autoclaved peat moss exposed to various temperatures was assessed by ability to infect floating potato leaf discs. Infectivity of propagules in peat was measured after 0, 21, 35, 63, and 79 days of exposure to temperatures ranging from -33 C to 20 C. Propagules exposed to temperatures below freezing were no longer infective after 21 days. Exposure of propagules to temperatures of 15 or 20 C resulted in a rapid decline in infectivity over time; by the final sampling date, none were infective. In contrast, propagules exposed to a temperature of 5 C for 79 days remained infective.